Adoption of a Leucaena-based Cattle Fattening System in the Dompu District of Nusa Tenggara Barat, Indonesia - A, Muktasam; Dahlanuddin; Putra, Ryan A; Sriasih, Made; Fauzi, M Taufik; Tanaya, IGL Parta; Back, Penny J; Hickson, Rebecca; Pomroy, William E; Reid, Janet I; Anderson, Christopher W N; Morris, Stephen T (Asian Journal of Agriculture and Rural Development, 2022)
Cattle fattening using Leucaena (Leucaena leucocephala) as the source or the main component of the cattle’s diets is one of the proven innovations that can provide financial benefit to cattle farmers. The objective of this study is to evaluate the adoption of Leucaena-based cattle fattening and identify the factors contributing to the adoption and diffusion of these improved practices. A mixed method approach was used to understand the adoption of Leucaena and cattle management by local farmers who participated in the early stage (2017) and those who participated in the later stages of the project (2018–2020). The study showed that male Bali cattle (Bos javanicus) that were fed Leucaena-based diets grew two times faster than cattle fattened on grasses. This increased live weight gain and, subsequently, faster sales and increased profits. This may account for the rapid adoption and diffusion of Leucaena-based cattle fattening in Dompu through farmer-to-farmer learning, effective facilitation, demonstration trials, and linking farmers to end markets. To sustain the practice change, the project facilitated the development of an agribusiness support center (ASC). Sustaining the ASC requires further efforts that include internalization of the project outcome into the local government program.